Fluorapophyllite-(NH4), NH4Ca4(Si8O20)F⋅8H2O, a new member of the apophyllite group from the Vechec quarry, eastern Slovakia. (1st August 2020) - Števko, Martin; Sejkora, Jiří; Plášil, Jakub; Dolníček, Zdeněk; Škoda, Radek
Abstract: The new mineral fluorapophyllite-(NH4 ), ideally NH4 Ca4 (Si8 O20 )F⋅8H2 O, was found at the Vechec andesite quarry located near Vechec village, Vranov nad Topľou Co., Prešov Region, Slovak Republic. It occurs in cavities of quartz–illite–saponite–tobelite xenolith embedded in pyroxene andesite. Fluorapophyllite-(NH4 ) is associated with calcite, tridymite, pyrite, chabazite-Ca and heulandite-Ca. It forms clusters, aggregates or crystalline crusts consisting of individual, well-developed crystals up to 4 mm in size, exhibiting the forms 110, 101 and 001. The mineral is colourless to light pink and translucent with white streak and vitreous to pearly lustre; it is non-fluorescent under ultraviolet radiation. The Mohs hardness is 4½ to 5, tenacity is brittle, fracture is irregular, and there is perfect cleavage on 001. The calculated density is 2.325 g cm –3 . Fluorapophyllite-(NH4 ) is optically uniaxial (+) with ω = 1.5414(5) and ɛ = 1.5393(8) (λ = 589 nm). It is non-pleochroic. The empirical formula (based on 29 O + F apfu) is [(NH4 )0.55 K0.32 Na0.07 Ca0.06 ]Σ1.00 (Ca4.01 Mg0.02 )Σ4.03 Si7.97 O20 [F0.84 (OH)0.16 ]Σ1.00 ⋅8H2 O. Fluorapophyllite-(NH4 ) is tetragonal, space group P 4/ mnc, a = 8.99336(9) Å, c = 15.7910(3) Å, V = 1277.18(3) Å 3 and Z = 2. The seven strongest X-ray powder diffraction lines are [ d obs in Å, (I, %)( hkl )]: 7.897(32)(002), 7.812(13)(101), 4.547(14)(103), 3.946(100)(004), 2.985(39)(105), 2.4841(11)(215) and 1.5788(12)(00.10). The crystal structure of fluorapophyllite-(NH4 ), refined to R 1 = 0.0299 for 743 unique ( I > 3σ I ) observed reflections, confirmed that the atomic arrangement is very similar to that of the other members of the apophyllite group. The new mineral is named according to the current nomenclature scheme for apophyllite-group minerals and is an NH4 dominant analogue of fluorapophyllite-(K), fluorapophyllite-(Na) and fluorapophyllite-(Cs).